Pengaruh Likuiditas Dan Struktur Modal Terhadap Profitabilitas Pada Pt Maha Properti Indonesia Tbk Periode 2015 – 2024 - Dea Salsabila; Ayu Puspa Lestiyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effect of liquidity proxied by the Current Ratio (CR) and capital structure proxied by the Debt to Equity Ratio (DER), both partially and simultaneously, on profitability proxied by Return on Assets (ROA) at PT Maha Properti Indonesia Tbk during the period 2015–2024. The research method used is a quantitative method with a descriptive approach. The research sample consists of the company’s annual financial statements, including balance sheets and income statements, over a ten-year observation period. Based on the results of the partial test (t-test), the liquidity variable (CR) shows a t-value smaller than the t-table value (0.067 < 2.36462) with a significance value (Sig.) greater than the significance level α (0.984 > 0.05). The capital structure variable (DER) also shows a t-value smaller than the t-table value (│−1.552│ = 1.552 < 2.36462) with a significance value (Sig.) greater than the significance level α (0.165 > 0.05). These results indicate that partially, liquidity and capital structure do not have a significant effect on profitability. Meanwhile, the simultaneous test (F-test) shows a significance value of 0.354, with an F-table value of 4.74. This indicates that the F-value is smaller than the F-table value (1.210 < 4.74), and the significance value (Sig.) is greater than the significance level α (0.354 > 0.05). Therefore, liquidity and capital structure simultaneously do not have a significant effect on profitability. The coefficient of determination (R²) is 0.045 or 4.5%, indicating that liquidity and capital structure contribute 4.5% to the variation in profitability. The remaining 95.5% is influenced by other variables not included in thi